Peran Unit Pelaksana Teknis Dinas Pelatihan Tenaga Kerja Kupang Terhadap Pendapatan Asli Daerah (PAD) Provinsi Nusa Tenggara Timur. - Atto, Aplonia; Pering, Yonatan; Anin, Vidensia Bergitha (P3M Politeknik Negeri Ambon, 2023)
Sources of original regional income revenue consist of: regional tax revenue, regional levy revenue, income resulting from the management of separated regional assets and other legitimate regional original income. In order to support PAD sources, regional governments seek to invest in various opportunities to increase regional revenues, especially opportunities to collect public funds outside of tax revenues and regional levies. The aim of this research is to determine the role of the Technical Implementation Unit of the Kupang Manpower Training Service on Regional Original Income. The population in this research is: all staff in the Technical Implementation Unit of the Manpower Training Service. The number of informants was 4 people and 6 respondents were tenants, both from legal entities, the business world and individuals using data from the last 3 years 2020-2022. Data collection techniques used interviews and observations. Descriptive research is research with the aim of describing a population, condition or event systematically and accurately. The data analysis used was qualitative descriptive. Results obtained: the contribution contributed to Regional Original Income (PAD) from the implementation of training shows an increase from 2021 amounting to Rp. 4,000,000,- and in 2022 the increase in PAD will be IDR. 41,900,000. From the data obtained from 2021 and 2022, it can be categorized that UPTD PTK (played a role) in increasing PAD, whereas in 2020 it was unable to carry out training and collaboration activities with third parties due to the Covid-19 pandemic so it was discontinued and did not get permission to carry out any activities. From these data it can be categorized that UPTD PTK (plays less of a role) in increasing PAD.Keywords: Role, Technical Implementation Unit, Regional Original Income